Polymerization behavior within adhesive layer of one- and two-step self-etch adhesives: A micro-Raman spectroscopic study - Wakae Sakano (2018)
This study investigated the polymerization behavior within the adhesive layer of one- and two-step self-etch adhesives at the dentincomposite interface. Dentin surfaces were applied with Clearfil S 3 Bond (TS), Clearfil S 3 Bond Plus (TSP) and Clearfil SE Bond (SE), and then placed with a light-curing resin composite. After water storage for 24 h, the bonded teeth were sectioned and polished perpendicular to the adhesive interface, and the degree of conversion (DC) of the adhesive layer between the dentin and composite were determined using micro-Raman analysis. For all the adhesives, the DCs of the adhesive layers significantly decreased near the adhesive-composite join (p < 0.05). For the maximum DC value (P max ) and the DC value at the adhesive-composite join (P itf ), TS was significantly lower than TSP and SE (p < 0.05). The polymerization of oxygen-inhibited layer at the top of the adhesive could not reach maximum DC even after polymerization of the overlying resin composite.